(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2014)
The antinociceptive activity of the methanolic extract of the leaves of Feronia limonia Linn. (Family Rutaceae) was investigated using acetic acid-induced writhing model and tail flick test in swiss albino mice. The extract produced about 26.01% ( p< 0.01), 39.88% ( p< 0.01) and 57.07% (p< 0.01) writhing inhibition at the dose of 100, 200 and 400 mg/kg of body weight respectively, which was comparable to the standard drug diclofenac sodium where the inhibition was about 63.58% (p< 0.01) at the dose of 25 mg/kg of body weight. All doses of extracts significantly (p<0.05) increased latency of flick tail in tail immersion method. The methanolic extract showed dose dependent antinociceptive activity in both type of test in swiss albino mice. Phytochemical investigations of the leaves extract indicate the presence of tannins, saponins, steroids, alkaloids and flavonoids. The preliminary study of the methanolic extract showed antinociceptive activity in both writhing and tail flick test in mice. http://dx.doi.org/10.3329/bjpp.v26i1-2.19962 Bangladesh J Physiol Pharmacol 2010; 26(1&2) : 21-24